2010
DOI: 10.1186/1477-7819-8-27
|View full text |Cite
|
Sign up to set email alerts
|

Stage II/III rectal cancer with intermediate response to preoperative radiochemotherapy: Do we have indications for individual risk stratification?

Abstract: BackgroundResponse to preoperative radiochemotherapy (RCT) in patients with locally advanced rectal cancer is very heterogeneous. Pathologic complete response (pCR) is accompanied by a favorable outcome. However, most patients show incomplete response. The aim of this investigation was to find indications for risk stratification in the group of intermediate responders to RCT.MethodsFrom a prospective database of 496 patients with rectal adenocarcinoma, 107 patients with stage II/III cancers and intermediate re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 36 publications
(44 reference statements)
1
10
1
1
Order By: Relevance
“…Furthermore, in patients younger than 69 years we did not find better survival rates, which is opposite to the results of other studies 27,28. Finally, we found increased TIMP-1 levels (≥170mg/mL) to be an independent risk factor for worse OS (p = 0.047).…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, in patients younger than 69 years we did not find better survival rates, which is opposite to the results of other studies 27,28. Finally, we found increased TIMP-1 levels (≥170mg/mL) to be an independent risk factor for worse OS (p = 0.047).…”
Section: Discussioncontrasting
confidence: 99%
“…Er scheint sich für eine weitere individuelle Risikostratifizierung zu eignen [112]. Unter der Voraussetzung einer umfassenden, standardisierten histopathologischen Aufarbeitung des Rektumresektates (nach TME Die integrierte anatomisch-metabolische Bildgebung mit Fluordesoxyglukose (FDG)-PET/CT gilt heute als ein etabliertes Verfahren [124].…”
Section: × Gy Versus Rct Beim Rektumkarzinomauswirkung Auf Die Lebensunclassified
“…[6][7][8] In recent years, however, several studies have reported that preoperative CRT generally decreases the number of lymph nodes (LNs) in rectal cancer specimens or may even lead to a complete deletion of mesorectal LN. [9][10][11] In a previous study, we could demonstrate that nodal staging with a consistent LN yield of >30 nodes per specimen is feasible.…”
mentioning
confidence: 99%